(untitled) (Bioresearch Communications, 2023)
Pseudomonas aeruginosa and Acinetobacter baumannii are one of the most common causes of MBL mediated morbidity and mortality throughout the world. Day-by-day these isolates are showing increasing resistance trends to different antimicrobial agents. But there are few data in Bangladesh, the study was designed to observe the pattern of antimicrobial resistance, prevalence of MBL, AmpC and finally phylogenetic distributions. A total of 200 isolates were analyzed in this study, comprising of 100 MDR-carbapenem resistant P. aeruginosa and 100 MDR-carbapenem resistant A. baumonnii. Isolates were tested for antimicrobial susceptibility, AmpC test, phenotypic and genotypic detection of MBL production. Antimicrobial susceptibility tests demonstrated that out of the 100 P. aeruginosa isolates, 99% were resistant to ceftriaxone and cefixime followed by ciprofloxacin/amikacin/netilmicin (94%), imipenem (93%) and meropenem (91%). On the other hand, 100% of the studied A. baumannii isolates were resistant to ceftriaxone, co-trimoxazole, cefixime and meropenem followed by imipenem (99%), ciprofloxacin (97%), amikacin (95%) and ceftazidime (94%). P. aeruginosa and A. baumannii showed 48% and 32% carbapenemase, 34% and 25% AmpC and 92% and 35% MBL positive, respectively. Phylogenetic analysis of blaVIM gene of 16 P. aeruginosa showed similarities with the sequences from the global origin. Phylogenetic analysis of the blaNDM-1 gene sequences from 5 A. baumannii isolates (5%) revealed that 4 sequences from strains formed distinct lineages with that of the stains from India, while only one was found to be closely related to the sequences from global sources. This study found a high percentage of MBL production in MDR-carbapenem resistant P. aeruginosa (92%) and A. baumannii (35%) isolates. These findings indicate significant concern given the predominant socio-economic factors that promote the rapid spread of antimicrobial resistance and infectious diseases in developing countries such as Bangladesh. Bioresearch Commu. 9(2): 1276-1284, 2023 (July)